2016
DOI: 10.1002/2016jb013022
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variation of frictional strength in an earthquake swarm in NE Japan caused by fluid migration

Abstract: Temporal variations of the fault frictional strength was investigated based on the diversity of focal mechanisms in the source area of the Yamagata‐Fukushima border earthquake swarm, a significant earthquake swarm that occurred in central Tohoku, NE Japan, which started just after the 2011 M9.0 Tohoku‐Oki earthquake. The focal mechanisms of events in this swarm activity were determined using P wave polarity data as well as short‐period (1.5–2.5 Hz) waveform data from the direct P wave. The stress field in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
47
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 42 publications
(73 reference statements)
4
47
1
Order By: Relevance
“…The remarkable earthquake swarm activity that occurred near the border between Yamagata and Fukushima Prefectures in NE Japan (Figure ) after the 2011 M 9.0 Tohoku‐Oki earthquake is one example of such migrating swarms. Previous studies (Okada et al, ; Terakawa, Hashimoto, & Matsu'ura, ; Yoshida, Hasegawa, & Yoshida, ) have suggested that this swarm occurred in response to an increase in pore pressure due to fluids rising from below, induced by the EW extension caused by the Tohoku‐Oki earthquake (Yoshida et al, ). The source area of this swarm is located just beneath the caldera structure, which is believed to include shallow igneous bodies with hydrothermal fluids immediately below (Yoshida et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The remarkable earthquake swarm activity that occurred near the border between Yamagata and Fukushima Prefectures in NE Japan (Figure ) after the 2011 M 9.0 Tohoku‐Oki earthquake is one example of such migrating swarms. Previous studies (Okada et al, ; Terakawa, Hashimoto, & Matsu'ura, ; Yoshida, Hasegawa, & Yoshida, ) have suggested that this swarm occurred in response to an increase in pore pressure due to fluids rising from below, induced by the EW extension caused by the Tohoku‐Oki earthquake (Yoshida et al, ). The source area of this swarm is located just beneath the caldera structure, which is believed to include shallow igneous bodies with hydrothermal fluids immediately below (Yoshida et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The initiation of seismicity in this swarm was delayed until 7 days after the occurrence of the Tohoku‐Oki earthquake, possibly the time needed for the fluids to move upward and increase the pore pressure. Temporal variation in the relative magnitude of frictional strength was estimated, based on a diversity of focal mechanisms, by Yoshida, Hasegawa, and Yoshida (), as shown in Figure b. The frictional strength was at first small, but steadily increased with time, and then became approximately constant.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Heinicke et al [] speculate that this interaction leads to an extensive hydrothermal alteration of crustal rocks at focal depth, erosion of faults, and gradual fault weakening, resulting finally in fault failure. A variation of frictional strength of faults caused by fluid migration is also reported by Yoshida et al [] for an earthquake swarm in NE Japan. The fault weakening processes are recognized to be important also for standard seismic sequences and can span various time scales.…”
Section: Introductionmentioning
confidence: 99%